What makes people quit tobacco and succeed at it?: An exploratory analysis of smoked and smokeless tobacco from India - Ssabbagh, Majd al; Elango, Varalakshmi; Winkler, Volker (Preventive medicine, 2022)
Tobacco cessation is a key component of WHO's Framework Convention on Tobacco Control. However, success rates decline significantly from intending to quit tobacco, through attempting and becoming a successful quitter. Among Indian adults, the prevalence of smoking and smokeless tobacco use was 10.7% and 21.4% respectively in 2016. Furthermore, 9% of all deaths were estimated to be attributable to tobacco. This study aims to explore associations of socio-demographic, environmental and behavioural dimensions of tobacco users with the process of successful quitting. Multivariable logistic regression analyses were conducted to study (i) attempting to quit and (ii) being a successful quitter for smoked and smokeless tobacco, using cross-sectional Global Adult Tobacco Survey (GATS) datasets for India (2009-10 and 2016-17), where data was pooled from the two surveys (n = 53,463). Advise to quit by health care provider was associated with quit attempts of smoking (1.82, 95% CI: [1.51; 2.20]), and smokeless tobacco (1.71, 95% CI: [1.45; 2.01]). Never being exposed to smoke at home was the strongest environmental factor for successful smoking cessation (4.04, 95% CI: [2.59; 6.31]). Noticing label warnings and advertisements was also associated with attempting to quit smoked and smokeless tobacco. Being a former smoker/smokeless tobacco user was positively connected with attempting to quit the current use of the other tobacco form. We recommend strategies to promote smoke-free homes, and incorporating ‘tobacco cessation advocacy’ into the curriculum of health care workers. Strengthening the tobacco control law and program promulgated in India since 2003 and its implementation would significantly promote tobacco cessation.
Gesehen am 13.07.2022